Struktur Komunitas Mangrove di Bale Mangrove Poton Bako Jerowaru Lombok Timur - Rizki Dwi Saputra; Agil Al Idrus; Baiq Sri Handayani (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
The mangrove ecosystem in Bale Mangrove Poton Bako area has an important ecological and economic role for the people of East Lombok, but data regarding its community structure needs to be updated as a basis for management. This study aims to analyze the structure of the mangrove community in the area. The method used is the line transect and plot method spread across three observation clusters with plot sizes of 10x10 meters (trees), 5x5 meters (saplings), and 2x2 meters (seedlings). The results showed the presence of 5 mangrove species from 3 families, namely Avicennia marina, Rhizophora apiculata, Rhizophora mucronata, Rhizophora stylosa, and Sonneratia alba. Based on species composition, the study area is dominated by Rhizophora mucronata (38%). The density of tree-level species (500-667 trees/ha) is categorized as “sparse”, but the canopy cover reaches 80% (very dense category) in accordance with the standards of the Minister of Environment Decree No. 201 of 2004. Rhizophora mucronata dominates Clusters I and II with the highest Importance Value Index (IVI) (151.33-211.21%), while Sonneratia alba dominates Cluster III (IVI 180.31%). This area exhibits high regeneration potential, with a seedling density of up to 22,500 individuals/ha under optimal environmental conditions (salinity 29-31 ppt; pH 7.2-7.6).